Venous thromboembolism prevention through the use of novel Factor Xa inhibitors. Issue 2 (17th February 2019) - Al-Hillan, A.; Bajwa, R. S.; Cheema, A.; Ezeume, A.; Gor, S.; Mahida, H.; Kountz, D. S.
ABSTRACT: The risk of a venous thromboembolic event is not limited to the pre-hospital, hospital, or immediate post-hospital period. Because of challenges with data collection, the risk of venous thromboembolism (VTE) up to 3 months post-hospitalization for patients with acute and serious medical problems in the setting of chronic disease and/or risk factors for VTE is probably under reported. The growing acceptance and indications of direct oral anticoagulants (DOACs) now includes an indication for VTE prevention for one of the Factor Xa agents. In this paper, the authors explore the issue of VTE in the extended post-hospital period and strategies to provide protection from these morbid and potentially mortal events with oral anticoagulants.